Impact of Farmers’ Adoption of Good Agricultural Products on Total Factor Productivity Change: The Case of Grape and Apple Production in Vietnam - Vũ Thi Minh; Trần Mạnh Dũng; Đào Quyết Thắng (My University, 2018)
Impact of Farmers’ Adoption of Good Agricultural Products on Total Factor Productivity Change: The Case of Grape and Apple Production in Vietnam
Keywords: Farmers' adoption; TFP change; Grape & Apple